Nitrification inhibitor nitrapyrin does not affect yield-scaled nitrous oxide emissions in a tropical grassland - Pérez Castillo, Ana Gabriela (2021)
Urea is the most common nitrogen (N) fertilizer used in the tropics but it has the risk of high gaseous nitrogen (N) losses. Use of nitrification inhibitor has been suggested as a potential mitigation measure for gaseous N losses in N fertilizer-applied fields. In a field trial on a tropical Andosol pastureland in Costa Rica, gaseous emissions of ammonia (NH3) and nitrous oxide (N2O) and grass yield were quantified from plots treated with urea (U; 41.7 kg N ha–1 application–1) and urea plus the nitrification inhibitor nitrapyrin (U + NI; 41.7 kg N ha–1 application–1 and 350 g of nitrapyrin for each 100 kg of N applied) and control plots (without U and NI) over a six-month period (rainy season). Volatilization of NH3 (August to November) in U (7.4% ± 1.3% of N applied) and U + NI (8.1% ± 0.9% of N applied) were not significantly different (P > 0.05). Emissions of N2O in U and U + NI from June to November were significantly different (P < 0.05) only in October, when N2O emission in U + NI was higher than that in U. Yield and crude protein production of grass were significantly higher (P < 0.05) in U and U + NI than in the control plots, but they were not significantly different between U and U + NI. There was no significant difference in yield-scaled N2O emission between U (0.31 ± 0.10 g N kg–1 dry matter) and U + NI (0.47 ± 0.10 g N kg–1 dry matter). The results suggest that nitrapyrin is not a viable mitigation option for gaseous N losses under typical N fertilizer application practices of pasturelands at the study site.